Republicanism in Russia community before and after Communism - Charchordin, Oleg Valerʹevič 1964- (Harvard University Press, 2018)
Marxism was the loser in the Cold War, but Oleg Kharkhordin is not surprised that liberal democracy failed to take root after the Soviet Union's dissolution. He suggests that Russians find a path to freedom by looking to the classical tradition of republican self-government and civic engagement already familiar from their history and literature....